2012
DOI: 10.1371/annotation/4cafed66-fb84-4589-a001-131d9c50aea6
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Persistence of Borrelia burgdorferi in Rhesus Macaques following Antibiotic Treatment of Disseminated Infection

Abstract: The persistence of symptoms in Lyme disease patients following antibiotic therapy, and their causes, continue to be a matter of intense controversy. The studies presented here explore antibiotic efficacy using nonhuman primates. Rhesus macaques were infected with B. burgdorferi and a portion received aggressive antibiotic therapy 4-6 months later. Multiple methods were utilized for detection of residual organisms, including the feeding of lab-reared ticks on monkeys (xenodiagnosis), culture, immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Furthermore, in a ceftriaxone-treated mouse model that investigated the persistence of non-cultivable B. burgdorferi by monitoring the pathogen DNA level for 12 months, the Borrelia DNA level initially cleared after ceftriaxone treatment but resurfaced after 12 months, suggesting persistent infection [17,23]. In another non-human primate study, viable B. burgdorferi were recovered by xenodiagnoses and in vivo cultures from both antibiotic-treated and untreated rhesus macaques infected with B. burgdorferi [20,21]. Furthermore, intact spirochetes were observed in the brain and heart of B. burgdorferi-infected rhesus macaques 8-9 months after antibiotic treatment [22].…”
Section: Borrelia Dna Persists In the Long Termmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in a ceftriaxone-treated mouse model that investigated the persistence of non-cultivable B. burgdorferi by monitoring the pathogen DNA level for 12 months, the Borrelia DNA level initially cleared after ceftriaxone treatment but resurfaced after 12 months, suggesting persistent infection [17,23]. In another non-human primate study, viable B. burgdorferi were recovered by xenodiagnoses and in vivo cultures from both antibiotic-treated and untreated rhesus macaques infected with B. burgdorferi [20,21]. Furthermore, intact spirochetes were observed in the brain and heart of B. burgdorferi-infected rhesus macaques 8-9 months after antibiotic treatment [22].…”
Section: Borrelia Dna Persists In the Long Termmentioning
confidence: 99%
“…The question is whether or not the persistent symptoms are related to ongoing spirochetal infection despite antibiotic therapy [15]. In vivo animal studies with immunocompetent mice, dog, and non-human primate models have identified a surviving, but not cultivatable form of B. burgdorferi that can withstand antibiotic treatment [16][17][18][19][20]. Recent studies on rhesus macaques and mice confirmed these observations by demonstrating a metabolically active, persistent B. burgdorferi post-treatment in antibiotic-treated animals [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Borrelia, the existence of antibiotic persister cells has been demonstrated by numerous groups, both in vitro and in vivo with animal models and human patients [262][263][264][265][266]. Notably, this persister fraction has been found to tolerate high concentrations of antimicrobials that exceed levels considered clinically achievable [262].…”
Section: Borrelial Antibiotic Persistencementioning
confidence: 99%
“…While the majority of Lyme disease patients can be cured if treated promptly with the standard two- four-week doxycycline, amoxicillin, or cefuroxime therapy [3], at least 10%–20% of Lyme patients have lingering symptoms such as fatigue, muscular and joint pain, and neurologic impairment even six months after the antibiotic treatment—a set of symptoms called post-treatment Lyme disease syndrome (PTLDS) [4]. While the cause of PTLDS is unknown, several possibilities are likely to be involved, including autoimmune response [5], immune response to continued presence of antigenic debris [6], tissue damage as a result of Borrelia infection and inflammation, co-infections [7], as well as persistent infection due to B. burgdorferi persisters that are not killed by the current antibiotics used to treat Lyme disease [8,9,10]. Various studies have found evidence of B. burgdorferi persistence in dogs [11], mice [8,9], monkeys [10], as well as humans [12] after antibiotic treatment; however, viable organisms are very difficult to culture from the host after antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%